PENGEMBANGAN FITUR VISUAL AUDIO, SIMULASI UJIAN DAN TAMPILAN WEBSITE PERFORMANCE CHECK BAGI PERSONEL AERONAUTICAL COMMUNICATION DI PERUM LPPNPI CABANG BALIKPAPAN - Ilham Lucky Lorentza; Didi Hariyanto; Ramining Puspitaningsih (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study uses a Research and Development (R&D) research methodology. The development that has been carried out is an advancement of website performance check, where features that previously did not exist have become available. These features are Video Conferencing, Voice Recorder, Message (Chat) features and Counseling Materials. For Aeronautical Communication Officer, licenses and ratings are indispensable as evidence or requirements for carrying out their duties. Based on the PM 14 of 2019 document concerning Civil Aviation Safety Regulations part 69 (Civil Aviation Safety Regulations part 69) concerning License, Rating, Training, and Skills of Aviation Navigation Personnel. It was explained that in order to maintain the rating, flight communication personnel were required to take a rating exam which was held once a year. Perum LPPNPI Balikpapan Branch is one of the operators of Indonesian flight navigation under the auspices of the State-Owned Enterprises. Perum LPPNPI, the Balikpapan branch located at Sultan Aji Muhammad Sulaiman Sepinggan Airport, Balikpapan is located in the province of East Kalimantan. Where every personnel from ATC, ACO, and engineering are required to take a rating test. With this, a more practical and efficient testing method is needed for users/participants and checkers. The implementation of the rating test using the website using the latest features is a result of this research. It is expected that the implementation of the rating test which is applied annually continues to use the website, is carried out periodically to measure the quality of each personnel and also extends the validity period of the website, so that the website does not expire by maintaining it every year.